2018
DOI: 10.3390/app8030444
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Aberration Compensation and Coherent Noise Suppression in Digital Holography

Abstract: Digital holographic microscopy (DHM) is a topographic measurement technique that permits full-field, nondestructive, dynamic, quantitative amplitude, and phase-contrast imaging. The technique may realize the lateral resolution with submicron scale and the longitudinal resolution with subnanometer scale, respectively. Improving imaging quality has always been the research focus in DHM since it has a direct effect on the precise topographic measurement. In this paper, the recent progress on phase aberration comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…The quality metrics can be extended programmatically by implementing the Quality interface. The double wavelength unwrapping method uses the subtraction method described in several places in the literature [12,16,28].…”
Section: Fiji Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…The quality metrics can be extended programmatically by implementing the Quality interface. The double wavelength unwrapping method uses the subtraction method described in several places in the literature [12,16,28].…”
Section: Fiji Programmingmentioning
confidence: 99%
“…The presence of the lens causes a magnification of the object according to the rules of geometric optics, with a resulting quadratic phase aberration. Removal of this aberration, and others such as astigmatism, may be done by a variety of methods; the literature is extensive, with recent reviews [11,12]. One of the most easily performed, if the data permit, is to define a "reference hologram" that is subtracted from the rest of the holograms in the data set prior to reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the uncountable amount of work that has been devoted to speckle and the everincreasing number of research publications related to these methods, multiple review works have been published with the most successful approaches for a given technique. In Digital Holography, recent and complete compilations of speckle denoising methods are available in [106,107], one of them having been published in the first months of 2020; additionally, a comprehensive study of the suppression of other inaccuracy sources can be found in [108],…”
Section: Existing Noise Reduction Methodologiesmentioning
confidence: 99%
“…Here, we describe some of the methods that we have chosen to compare with our approach, that is, AME method. For more comprehensive overview of phase aberration compensation methods we recommend an up‐to‐date paper . Our constraints are the following: procedure needed to be applicable automatically, without the need for selecting specimen‐free region and it should be applicable without readjustment of the hardware.…”
Section: Aberrations Correctionmentioning
confidence: 99%